Factors Affecting the Quality of Audit Process “The External Auditors’ Perceptions” - Almasria, Nashat Ali (Accounting Department,, 2022)
Purpose — This research aims to investigate the factors that affect audit quality, including the board of directors’ characteristics and performance, the audit committee's responsibilities, internal audit factors and performance, and the quality of the external audit. Design/methodology/approach—This study expanded on previous research that has used different proxies to measure audit quality. It employed a questionnaire to measure audit quality and internal governance mechanisms by adopting some practical indicators from previous literature that could reflect and affect audit quality. Findings — According to the regression results, it has been found that there is a strong positive relationship, which is statistically significant, between the work performance of internal auditors and the audit quality (β =0.280, p=.000); the strongest relationship was between audit quality and work performance, and it contributes to the model, and this is consistent with prior studies. Further, the board of directors’ responsibilities has been determined to have a significant impact on audit quality where the coefficient of determination is .085 at a significant level. Practical implications — Due to prevalent corporate scandals and audit failures worldwide in recent years, there has been a renewed interest in the relationship between Internal Corporate Governance Mechanisms (ICGM) and External Audit Quality (EAQ). Audit quality and corporate governance mechanisms are significant aspects of today’s business practices. Hence, these issues have evoked interest and received the attention of regulators, researchers, and practitioners. They have become the centre of the argument due to their role in boosting investors’ confidence and improving the reliability of financial reports. Originality/value—The current study contributed to the auditing and corporate governance literature. It expanded on previous research that used different proxies to measure audit quality and factors influencing audit quality. Keywords — Pancasila, accounting education, accountant, financial fraud Paper type — Research Paper